Incision Location Predicts 30-Day Major Adverse Events after Cosmetic Breast Augmentation: An Analysis of the Tracking Outcomes and Operations for Plastic Surgeons Database. Issue 5 (November 2021) - Valente, Denis S.; Pannucci, Christopher J.; King, Timothy W.; Gutowski, Karol A.; Gusenoff, Jeffrey A.; Rodby, Katherine A.; Zanella, Rafaela K.; Friji, M.T.; Day, Kristopher M.; Kaye, Alison E.
Abstract : Background: Enhanced understanding of early postoperative adverse events will improve patient counseling and preoperative risk modification to decrease complications in implant-based breast augmentation. This study seeks to evaluate the early major adverse events following cosmetic breast augmentation. Methods: A retrospective cohort analysis of the Tracking Outcomes and Operations for Plastic Surgeons database was performed to identify any women undergoing augmentation mammaplasty with an implant between 2008 and 2016. Results: A total of 84, 296 patients were studied. Major adverse events were identified in 0.37 percent. Seroma requiring drainage was observed in 0.08 percent, hematoma requiring drainage was observed in 0.15 percent, deep wound disruption was observed in 0.09 percent, and implant loss was observed in 0.11 percent. The authors identified multiple independent predictors of major adverse events, including body mass index greater than 30 kg/m 2 (relative risk, 2.05; p < 0.001), tobacco use (relative risk, 2.25; p < 0.001), and diabetes mellitus (relative risk, 1.8; p < 0.05). Use of a periareolar incision significantly increased the risk of developing an early postoperative complication (relative risk, 1.77; p < 0.001). Conclusions: The findings of this study indicate an early major adverse event rate following cosmetic breast augmentation with implants of 0.37 percent. The authors identified multiple independent predictors of major adverse events, including body mass index greater than 30 kg/m 2, tobacco use, and diabetes mellitus. In addition, when controlling for other factors, periareolar incision significantly increased the risk for major adverse events, when compared to an inframammary incision. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.